Comportamiento de la morosidad del crédito hipotecario y de consumo en la Caja Municipal de Ahorro y Crédito Maynas Sociedad Anónima en el periodo 2019-2023 - Garcia Chavez, Alexandra (2025)
This research analyzes the behavior of mortgage and consumer loan delinquency at Maynas Municipal Savings and Crredit Bank S.A.. during the 2019–2023 period. A quantitative, descriptive, and non-experimental approach was used, based on secondary data provided by the Superintendency of Banking, Insurance, and Pension Funds (SBS). The results reveal that both mortgage and consumer loan delinquency remained at medium levels, contradicting the initial hypothesis of high levels. An increase in the mortgage loan delinquency rate was identified, especially in 2023, reaching 11.47%, while consumer loans maintained reasonable rates, below 5%. Determining factors include the economic effects of the pandemic, loan rescheduling policies, state intervention through programs such as Reactiva Perú, and the entity's performance in the credit evaluation process. It is concluded that adequate risk management, combined with macroeconomic measures, has kept delinquency rates at manageable levels. The research provides relevant input for improving credit evaluation, monitoring, and refinancing policies.